Ethical Challenges Faced by Senior Dental Students and General Dentists - F Rashidi Maybodi; A Haerian Ardakani; M Khabazzadeh Yazdi (Islamic Azad University, 2021)
Background: General familiarity with medical ethics sometimes does not meet the needs of dentists. The aim of this study was to evaluate the ethical challenges faced by senior dental students and dentists. Methods: In this cross-sectional study, 50 senior dental students and 50 dentists were selected from Yazd city, Iran. A questionnaire with three domains (demographic information, hypothetical scenarios, and some three-choice questions about ethical issues) was used to collect data, and the data were analyzed by the Chi-square test. Results: The mean age of students and general dentists was 24±2 and 30±2 years, respectively; 42% of the respondents were males, and 58% were females. Except for one item (dentist's right to refuse treatment) (P<0.05), no significant difference was found between the two groups (P>0.05). The most common challenges faced by the participants were compromising treatment due to cost issues (77.1% of students and 71.4% of dentists) and noticing sub-standard treatments performed by other dentists (64% of students and 58% of dentists). Unawareness about the right way to criticize other dentists was the least commonly reported challenge (28% of students and 36.7% of dentists). A significant difference was found in the frequency of encountering sub-standard treatments performed by other dentists between the two groups (P=0.031). A significant difference in the frequency of a particular challenge between males and females was seen only in one item (disagreement with other colleagues on the appropriate treatment plan) and only in the students' group (P= 0.040). Conclusion: This study showed that dental practitioners had faced a variety of ethical challenges, that need to be addressed in dental education. However, the results of this study may not be generalizable to other cities.